A self-management of e-learning in COVID-19 pandemic among Islamic studies students in Universiti Teknologi MARA, Shah Alam / Mohd Amzari Tumiran ... [et al.] - Tumiran, Mohd Amzari; Daud, Mohd Zaid; Zarmani, Nur Farhani; Mohammad, Nasharuddin; Wan Ruzali, Wan Adriyani (Universiti Teknologi MARA, 2021)
Education was impacted by the COVID-19 pandemic in a variety of ways. The e-learning concept was normalized especially in higher education levels. However, the effectiveness of self-management elements in the present pandemic situation is unclear. This study focuses on assessing the selfmanagement efficiency relationship between time, cost, and self-regulation of e-learning in the COVID-19 atmosphere among students of Islamic studies in a Malaysian public institution of higher learning. Students of Academy of Contemporary Islamic Studies in the Universiti Teknologi MARA Shah Alam, Selangor were involved as respondents (n = 457). Data were collected using online questionnaires and analyzed using IBM SPSS Statistics. A reliability instrument test has been conducted. Cronbach’s Alpha analysis indicated that the instrument is acceptable for the research (α = 0.791). Spearman rho analysis indicated a significant positive moderate and lowlevel correlation values (ρ < 0.05) for e-learning management efficiency between: (a) self-regulation and time (rs = 0.499); (b) time and cost (rs = 0.269); and (c) cost and self-regulation (rs = 0.224). This study suggests that the students of Islamic studies need to give more attention to time self management as this aspect was indicated as relatively low compared to cost management and self-regulation. Unfortunately, the worldwide scope and pace of today’s educational turbulence are unusual, and if it remains, it may result in mental harm and suffering. It is strongly recommended to develop technical, economical, and psychological support for students in facing e-learning in pandemic challenges. A cross-sectional study on the different universities is recommended for further study.